Word Sense Disambiguation By Using Domain Knowledge - Wei, Jan Lee; Edwin, Mit (IEEE, 2011)
Over the decades, lot of studies had been carried out to suggest different approaches for Word Sense Disambiguation (WSD) process. From times to times, different approaches had been suggested to define the sense of a polysemous word. In this paper, a WSD approach with the domain knowledge will be discussed. In this approach, by using Wordnet, domains of each single word will be defined and a process of defining the best domain to be assigned to that particular word will be carried out. A method of calculating the weight of each domain to its corresponding word will be discussed. According to the weight assigned to each domain, the sense of the ambiguous word will be identified.